Pre-service knowledge, perception, and use of emergency contraception among future healthcare providers in northern Ghana - Shamsudeen Mohammed; Abdul-Malik Abdulai; Osman Abu Iddrisu (BMC, 2019)
Abstract Background Emergency contraception, if used properly, can prevent up to over 95 % of unwanted and mistimed pregnancies. However, a number of obstacle including healthcare providers knowledge, perception, and attitude towards emergency contraception (EC) prevent women and adolescents from having access to EC. Methods This was a cross-sectional study among 191 female final year nursing and midwifery students of Tamale Nurses and Midwives Training College in the Northern Region of Ghana. Purposive sampling method was used to sample 100 students from the nursing programme and 91 from the midwifery programme. Chi-square and Fisher's exact tests were performed to determine factors associated with awareness about EC and use of EC. Results Over four-fifths, 166(86.91%), of the participants indicated they had heard about EC prior to the study. Majority (80.10%) of the participants correctly indicated the time within which to take emergency contraceptive pills (ECPs). More than half, 105(54.97%), of the participants did not know the appropriate time within which to use IUD as EC. Almost four-fifths, 74(38.74%), of the participants indicated it is morally wrong to use EC and more than half, (n = 104, 54.45%), of them said EC use promotes promiscuity. Only 49(25.65%) participants said they had ever used ECP. Of the number that indicated ever-using ECP, 36(73.47%) cited condom breakage or slippage as the reason for using the method. Conclusion Though there was a relatively high level of EC awareness and knowledge among the students, some students lacked detailed knowledge about the method, especially the use of IUD as EC. We found that it was easy to access EC in the study area but the use of EC was low among the students. Most of the students demonstrated a positive attitude towards EC, but many of them believed EC encourages promiscuous sexual behaviour and that it is morally wrong to use EC. The curriculum for nursing and midwifery education should provide opportunity for detailed information and practical knowledge on EC to demystify negative perceptions and attitudes of nursing and midwifery students towards EC and other forms of contraception and to improve their knowledge on EC.